Cosmological models in certain scalar-tensor theories - Ram S.; Singh J.K. (My University, 2025)
Exact solutions of Einstein field equations are obtained in the scalar-tensor theories developed by Saez and Ballester (1985) and Lau and Prokhovnik (1986) when the line-element has the form {Mathematical expression}where h, A and B are functions of t only. The solutions are spatially homogeneous, locally rotationally symmetric and admit a Bianchi I group of motions on hypersurfaces t = constant. The dynamical behaviours of these models have also been discussed. © 1995 Kluwer Academic Publishers.